Ethical Philosophical Values in the Short Story "God Sees the Truth, But Waits" by Leo Tolstoy - Pismawenzi, Pismawenzi; Jamaldi, Jamaldi; Putri, Endrika Widdia (Jurnal Fuaduna : Jurnal Kajian Keagamaan dan Kemasyarakatan, 2023)
Every literary work must have value in it. An in-depth analysis is required to capture and understand the value. This article analyze the ethical philosophy matters in the short story â€œGod Sees the Truth, but Waitsâ€ by Leo Tolstoy (1828â€“1910)â€”a writer and philosopher from Russia. This article departs from a qualitative study using interpretation and analysis methods. This study finds that the short storyâ€™s philosophical message relates to Godâ€™s plan for His creation; God knows the truth about what would happen to His creation but waits for the best time to show His wisdom. The ethical philosophy values Aksionov owns include submission, truth, justice, and forgiveness. These four values lived on in Aksionov after his wound. He understands that wounds are God's way of getting him closer to Him and making him a better human being.